Fear-enhanced visual search persists after amygdala lesions - PIECH, RICHARD (Elsevier, 2010)
Previous research has indicated that the amygdala is a critical neural substrate of the emotional modulation of attention. However, a recent case-study suggests that the amygdala may not be essential for all types of emotion-attention interactions. In order to test this hypothesis, we assessed the visual-search performance of patients with unilateral amygdala lesions, matched controls, and medication-matched epilepsy patients with intact amygdalae. All participants completed a visual-search task consisting of trials in which (1) an emotional target was embedded amongst neutral distractors, (2) a neutral target was embedded amongst emotional distractors, or (3) a neutral target was embedded amongst neutral distractors. All participant groups, including those with amygdala lesions, detected emotional targets more efficiently than neutral targets. These data indicate that the amygdala is not necessary for emotion-guided visual search and suggest that other mechanisms beyond the amygdala help guide attention toward threatening stimuli.
PUBLISHED
Keywords: Psychology; Human amygdala